Sentiments - Matimba, Jackson, 1978- (Project Muse, 2019)
This collection by Zimbabwean poet, Jackson Matimba, gives us spellbinding insights into life. The poems carry various themes; "Sentiments of the earth" focuses on global warming and the aspects of our lifestyle which are effecting the climate of the world. The diary of a soldier" speaks of the emotional challenges that every soldier experiences when away from home, and also the problems faced by family during long absences from home. The poet also tackles the issues of migration in the poem, "Sentiments of migration."